"Disasters threaten livelihoods, and people cope, adapt and make transformational changes": Community resilience and livelihoods reconstruction in coastal communities of Bangladesh. (September 2021) - Uddin, M. Salim; Haque, C. Emdad; Khan, Mohammad Nuruzzaman; Doberstein, Brent; Cox, Robin S.
Abstract: In the face of serious disruptions to local livelihoods and asset bases by extreme climatic events, it is paramount to reconstruct but also to transform and diversify livelihoods. However, the literature on these aspects is scant. In this paper, we posit that two frameworks, namely the livelihood strategy approach and community resilience thinking, are useful tools for effectively analyzing post-disaster transformational changes. In the empirical context of coastal communities of Bangladesh, our study specifically examines the changes experienced in livelihood assets due to Cyclones Sidr and Aila. Two coastal communities, namely Nilganj and Dhulasar Unions in the Kalapara Upazila of Patuakhali District, were selected to analyze the strategies used by local people to cope with and adapt to cyclone and storm surge disaster-shocks. Primary data were collected from three sources: a socioeconomic survey of 300 households, eight focus group discussions, and 20 key informant interviews. Our findings reveal that a significant number of cyclone victims were displaced from their homes by recent severe cyclones, changed their occupations – both intra- and intersectorally – and confronted increased consumption and social costs. We observed significant differences in impacts between farmers and those engaged in other occupations, such as fishing, with the latter being far more likely to change occupation post-disaster. The study uncovered significant evidence that local people are learning to live with change and uncertainty by nurturing and combining various types of knowledge and social memory, generating diversified livelihood options, and self-organizing to enhance their resilience to future extreme weather events. Highlights: Post-cyclone livelihood trajectories of coastal community members are diverse and adaptive. Considerable proportion of cyclone-disaster victims make transformational changes. Social capital and social learning play vital roles in the transformational processes. In coastal Bangladesh, resilience building factors interact across temporal and spatial scale.